2020
DOI: 10.12741/ebrasilis.v13.e0820
|View full text |Cite
|
Sign up to set email alerts
|

Study of behavioral patterns and infection analyses in anopheline species involved in the transmission of malaria in Buriticupu and São José de Ribamar municipality, Maranhão State, Brazil

Abstract: Anopheles darlingi Root and Anopheles aquasalis Curry are the main vectors of malaria that occur in the State of Maranhão. Entomological surveys based on the behavior and infectivity of these vectors are important for the elaboration of disease control strategies. The objectives of this work were to study the behavioral patterns of mosquitoes, determining population and hematophagic peaks, dietary preferences, infectivity rate and characterization of breeding sites in two municipalities in the State of Maranhã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…Overall, our findings support previous studies [ 13 , 16 , 17 , 35 , 45 ] that fish farming tanks play an important role as permanent breeding sites with high potential for promoting Anopheles larval development, especially for A . darlingi .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, our findings support previous studies [ 13 , 16 , 17 , 35 , 45 ] that fish farming tanks play an important role as permanent breeding sites with high potential for promoting Anopheles larval development, especially for A . darlingi .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is supported by the higher LIMH values ( Table 1 ) observed for this type of breeding site. Similar values were reported for São José de Ribamar, State of Maranhão (0.64), although Barros et al [ 45 ] captured only 75 Anopheles larvae in that locality. In this study, A .…”
Section: Discussionsupporting
confidence: 81%
“…Similar results to those observed in the present study were also reported in the state of Maranhão for A. albitarsis s.l., A. darlingi, and A. nuneztovari s.l., regarding HBR and with peaks occurring in the first time intervals (Barros et al, 2020). A second peak in the third time interval (21 -22 hours) was observed for A. darlingi.…”
Section: Discussionmentioning
confidence: 78%
“…We untangled how the direct and indirect paths of forest cover and water quality variables interact and shape anopheline assemblages in two seasons. Although previous studies determined how environmental variables at different spatial extents affected anopheline distributions in Amazônia, most studies focused on a single effect of an environmental variable or focused on single habitat types (terrestrial or aquatic) 22 , 23 , 41 , 42 . Our most important finding is that seasonality modulates the direct and indirect effects of forest cover on Amazônian anopheline larval distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality can also modulate water quality 21 . For example, in the dry season, lentic habitats are reduced, leading to increased primary production and dissolved solids and decreased pH, which are positively correlated with the presence of Anopheles species in aquatic systems 22 , 23 . Therefore, distinguishing the direct (mediated only by forest loss) and indirect (forest loss effects on larval habitats) effects of forest loss on mosquito diversity and abundance is fundamental for understanding and predicting mosquito assemblages.…”
Section: Introductionmentioning
confidence: 99%